Proses Pengeringan Sohun dengan Pemanasan Bertahap dalam Oven - Gerardus YosuaYosua; Winiati Pudji Rahayu (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Vermicelli or cellophane noodles is a type of noodle that is made from starch of sago or mung bean. Vermicelli has an appearance like string, spongy and slick in texture, and also transparent. Vermicelli production in small food industries employ the traditional technique of sunlight drying. The use of sunlight result in quality inconsistency, requires intensive labor and extensive drying area. These reasons encourage the authors to conduct a research on vermicelli drying process using oven dryer by gradual drying. Three heating treatments were tested, (A) 65oC for 10 minutes, 100oC for 10 min, and 140oC for 5 min, (B) 80oC for 10 min, 100oC for 10 min, and 130oC for 5 min, (C) 80oC for 15 min and 140oC for 10 min. The recommended drying treatment was at 80oC for 10 min, 100oC for 10 min, and 130oC for5 min. This processing condition produced vermicelli that is very similar to commercial traditional vermicelli. The vermicelli had water content of 13.09%, cooking loss of 11.67%, water absorption of 74.56%, and elongation value of 198%. Oven drying reduced the operational cost by up to 33% compared to that of sunlight drying. This indicated that oven drying can replace sunlight drying technique in traditional vermicelli process thus reducing processing time, production cost and improve vermicelli quality consistence.